Autocrine and paracrine regulatory functions of platelet serotonin. (18th August 2018) - Mammadova-Bach, Elmina; Mauler, Maximilian; Braun, Attila; Duerschmied, Daniel
Abstract: Platelets serotonin (5-hydroxytrytamine, 5-HT) uptake and storage in dense granules is tightly regulated by the serotonergic transport system in the blood. Several 5-HT transporters (5-HTTs) have been identified in the vasculature and blood cells, beyond them 5-HTT is the major 5-HT transporter in platelets. Abnormal 5-HT concentrations in the blood plasma or increased platelet 5-HT uptake or abnormal release contribute to the development of various diseases in the vasculature. Consequently, several clinical trials suggested the positive therapeutic effects of 5-HTT blockade in the circulation. Inhibition of 5-HT strongly attenuates autocrine and paracrine functions of platelets, influencing platelet aggregation, vascular contraction, permeability, tissue repair, wound healing, immunity and cancer. Here, we highlight the current state of basic biological research regarding the hemostatic and non-hemostatic functions of platelet-derived 5-HT in normal and disease conditions. We also describe the physiological consequences of targeting platelet 5-HT functions in thrombosis, stroke, inflammation and cancer to overcome common health problems.